2020
DOI: 10.3390/ijms21082932
|View full text |Cite
|
Sign up to set email alerts
|

Cold Atmospheric Plasma: A Powerful Tool for Modern Medicine

Abstract: Cold atmospheric plasma use in clinical studies is mainly limited to the treatment of chronic wounds, but its application in a wide range of medical fields is now the goal of many analyses. It is therefore likely that its application spectrum will be expanded in the future. Cold atmospheric plasma has been shown to reduce microbial load without any known significant negative effects on healthy tissues, and this should enhance its possible application to any microbial infection site. It has also been shown to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
138
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(199 citation statements)
references
References 161 publications
0
138
0
1
Order By: Relevance
“…To overcome these problems, we provide a novel vaginal cleaning device using plasmaactivated water and ultraviolet light. Recently, plasma source generation at atmospheric pressures has been of great interest for therapeutic applications, such as in coagulation, cancer treatment, and wound healing, in terms of plasma medicine [9][10][11]. Numerous studies have demonstrated plasmatreated sterilizing effects for bacterial infections and safe food preservation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, we provide a novel vaginal cleaning device using plasmaactivated water and ultraviolet light. Recently, plasma source generation at atmospheric pressures has been of great interest for therapeutic applications, such as in coagulation, cancer treatment, and wound healing, in terms of plasma medicine [9][10][11]. Numerous studies have demonstrated plasmatreated sterilizing effects for bacterial infections and safe food preservation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have analysed different cell lines in apoptotic content. The loss of cell viability and shrinkage of tumours occurred mainly as a result of apoptotic processes, as evident from the specific morphological changes and higher activity of apoptotic cascade members [28,151,228,229].…”
Section: Cap and Apoptosismentioning
confidence: 99%
“…Current trends in the establishment of CAP as a robust approach in anticancer therapy are also associated with the synergic use of plasma and nanotechnology or its application in the modulation of an immune response. The human immune system is significantly associated with cancer, and the ability of the immune system's modulation could overcome the capacity of cancer cells to suppress immune responses through several mechanisms, including cytokines, cell-based therapies, immune checkpoint blockades, and immunogenic cell death [228]. As immunotherapy has become an essential part of anticancer treatment, the CAP effect on the immune system was evaluated in several studies.…”
Section: Immunotherapy and Capmentioning
confidence: 99%
“…Cold atmospheric plasma (CAP) is ionized gas with high energy at relatively low temperatures. CAP generates reactive oxygen species (ROS), which can have many biological effects, including wound healing, sterilization, gene transfection, blood coagulation and cancer therapy [ 7 , 8 , 9 ]. Plasma medicine recently became a new area in human medicine [ 10 ] due to its mechanisms—including DNA damage, apoptosis, necrosis or autophagy by stimulating many ROS-mediated signaling pathways—leading to anticancer activity [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%